Representasi Makna Konflik Keluarga Pada Film Nanti Kita Cerita Tentang Hari Ini - Hakim, Aulia; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
The movie "Nanti Kita Cerita tentang Hari" (2020) tells the story of conflict in a family, which reflects a commonsituation that often occurs in society. Although many want a harmonious family, in reality every family has its ownconflicts. This research aims to understand the meaning of family conflict with a descriptive qualitative approachand uses Charless Sanders Pierce theory. The data collection method uses observation, documentation, andliterature study, with the object of research focusing on the movie "Nanti Kita Cerita Tentang Hari Ini". The resultsof the study identified two types of family conflicts, namely conflicts that can be resolved and conflicts that aresustainable.